Polyaniline-coated polyurethane foam for pressure sensor applications. (April 2016) - Muthukumar, N.; Thilagavathi, G.; Kannaian, T.
In this article, conductive composite foams were developed by in situ polymerization of aniline on polyurethane (PU) foam. After the polyaniline (PANI) deposition process on the interior surfaces of the porous PU foams, the nonconductive PU foams became conductive composites. The morphology of coating has been observed by means of scanning electron microscopy (SEM). The PANI-coated foam has been characterized chemically by means of energy-dispersive X-ray (EDX) and spectrometric analyses. The thermal characterization has been carried out by means of differential scanning calorimetery (DSC). The developed PANI-coated foam was subjected to compression tests in Zwick/Roell tensile tester, and electrical resistance was recorded during the tests to study the pressure-sensing mechanism. The stability of the developed sensor was characterized with respect to temperature and humidity using programmable environmental test chamber. The SEM studies revealed the deposition of PANI onto the PU surface, and the presence of sulfur content in PANI-coated foam was found through EDX analysis. The treated foam showed increase in light absorption during spectrometric analysis. From DSC studies, it was found that there is reduction in the melting temperature of PU foam after PANI coating. The conductive foam exhibited varying electrical properties with respect to compression. It was found that a linear relationship existed between change in electrical resistance and applied pressure up to 100 N/m 2, and the changes are less beyond this, making it suitable for pressure sensor applications for 0–100 N/m 2 pressure range.